Mindfulness and its relationship to creative self-efficacy among gifted students in the educational directorates of Hebron - Qabaga, Sawsan Jamal (Journal of Educational and Psychological Sciences, 2023)
The study aimed to investigate the relationship between mental alertness and creative self-efficacy among gifted students, employing a descriptive methodology, designed mental alertness and creative self-efficacy scales, and applied to a random sample of 235 academically outstanding male and female students from education directorates in Hebron.The study results showed that gifted students in the education directorates in Hebron had a high level of mental alertness and creative self-efficacy. The study also demonstrated no statistically significant differences in mental alertness and creative self-efficacy among gifted students according to the social gender variable. Statistically significant differences existed in the students' responses to mental alertness and creative self-efficacy scales attributed to the grade in favor of both the eighth and ninth grades, and the tenth and eleventh grades. Statistically significant differences in mental alertness were attributed to the economic level in favor of the high economic level. Statistically significant differences in creative self-efficacy were attributed to the economic level in favor of the average economic level. There is a positive and statistically significant correlation between mindfulness and creative self-efficacy among gifted students.In light of the study's findings, the researcher recommends harnessing financial and human resources to develop the skills of gifted students and provide alternatives for students with low economic status due to their inability to provide them considering the need for material resources.
Keywords: gifted students; mental alertness; creative self-efficacy